154k views
3 votes
3. **Determine the equation of the asymptote of y = 4(2)^x – 3.

1 Answer

1 vote

ANSWER

Horizontal asymptote: y = -3

Step-by-step explanation

The horizontal asymptote is the value the function takes when x→∞ or x→-∞. In this case, when x→∞ the function goes to ∞, but when x→-∞:


\lim _(x\rightarrow-\infty)4(2^{})^x-3=\lim _(x\rightarrow\infty)4(1)/(2^x)-3=\lim _(x\rightarrow\infty)4(1)/(2^x)-\lim _(x\rightarrow\infty)3=0-3=-3

The equation of the horizontal asyptote is y = -3

User Thomas Nicole
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.